Adverse Outcome Pathway on Aromatase inhibition leading to male-biased sex ratio via impacts on gonad differentiation - Santana Rodriguez, Kelvin J.. (OECD Publishing, 2023)
This adverse outcome pathway links inhibition of aromatase activity in teleost fish during gonadogenesis to increased differentiation to testis resulting in a male-biased sex ratio in the population, and ultimately, reduced population sustainability. Most gonochoristic fish species develop either as males or females and do not change sex throughout their life span. However, in species where sexual differentiation is controlled at least to some degree by environmental factors, there can be a window of development during gonadal differentiation that is sensitive to a variety of exogenous conditions. During this window, endocrine active chemicals, aromatase inhibitors in particular, have the potential to alter gonad development and sex differentiation. This AOP is referred to as AOP 346 in the Collaborative Adverse Outcome Pathway Wiki (AOP-Wiki)
Keywords: Environment